Metafora anatomi dalam Bahasa Melayu / Noor Hasnoor Mohamad Nor - Noor Hasnoor, Mohamad Nor (2017)
Lexical Semantic is a subfield of semantics. Semantics is generally defined as a study of meaning in a variety of genres; whereas lexical semantic is a focus of meaning on lexical level. This study focuses on metaphor; the idea that we can state the meaning of words in terms of their association with other words. This study aims to identify the metaphor of anatomy used in the Malay language, studying a particular part of the anatomy that gives certain meaning, and to analyze metaphor of anatomy based on the types of meaning. This study focuses on metaphors and the types of meaning, that used in the text, namely Karya Agung Pantun Melayu: Pantun Melayu Bingkisan Permata (2001) published by Yayasan Karyawan and Kurik Kundi Merah Saga (2005) published by Dewan Bahasa dan Pustaka. The corpora are processed using Antconc 3.2.4.w, a computer-aided software through concordance technique. The study uses Field Theory of Meaning (TMM) or Semantic Field Theory to identify the lexical that belongs to the same domain. Semantic approach is used to analyze the significance of the types of meaning. This study proves that there are elements of anatomy as a source of meaning in Malay Pantun. Each part of anatomy also has its own meaning shown through fields of meaning. The importance of context also clearly shown by this study, which means meaning is not complete without context.